"A day in the life" - telemedicine in family medicine and its relationship with practicing physicians' satisfaction: a cross-sectional study - Galia Zacay; Limor Adler; Yochai Schonmann; Joseph Azuri; Ilan Yehoshua; Shlomo Vinker; Anthony D Heymann; Shani Afek; Avivit Golan Cohen; Ilan Green; Robert Hoffman; Michal Shani (BMC, 2024)
Abstract Background Telemedicine has expanded rapidly in recent years, and many encounters that were conducted in person now take place remotely. This study aimed to assess primary care physicians' (PCPs) attitudes towards the different modalities of patient care. Methods This is a cross-sectional nationwide descriptive study conducted in Israel. We asked PCPs to document an entire workday and answer a short questionnaire after each visit. The questions addressed the type of visit (face-to-face, remote synchronous [telephone/video], or remote asynchronous [online requests]), the perceived quality of the visit, and the physicians' feelings at the end of each visit. Before documenting their working day, we asked the participants to answer a questionnaire about their general attitudes toward different modalities of medical visits and how they affect their well-being and burnout. Results Sixty physicians documented 2,025 visits, of which 39% took place in person, 36% stemmed from online patient requests, 18% were telephone meetings, < 1% were video meetings, and 6% consisted of other types of contact. Mixed effects logistic regressions were used to model the visits' evaluation. The odds ratios (ORs) for perceived medical quality of visits focused on medical tasks were lower for non-face-to-face visits: OR = 0.39, 95% CI 0.25-0.59 for remote synchronous, and OR = 0.14, 95% CI 0.09-0.23 for remote asynchronous. The perceived medical quality of visits focused on administrative tasks was lower for remote asynchronous than for face-to-face visits (OR = 0.31, 95% CI 0.14-0.65). We found no association between medical quality and patients, physicians, or clinic characteristics. The inappropriateness of the visit modality was also associated with lower medical quality (OR = 0.13, 95% CI 0.09-0.18). We found a correlation between perception of medical quality and physicians' feelings at the end of the visits, Spearman's r = 0.82 (p < 0.001). Conclusions A substantial portion of the visits was dedicated to administrative tasks and remote medicine. In comparison, physicians rated face-to-face visits' quality higher than remote visits. Policymakers should intervene to minimize administrative work, reduce PCPs' administrative workload, and direct patients to the optimal visit modality for their complaints. These steps would increase medical quality, reduce burnout, and mitigate the shortage of PCPs.